Comparative Epidemiological Assessment of Quality of Life (AQoL) Among Geriatric Population in Rural and Urban Satara During the COVID-19 Pandemic - Gaikwad, Rajesh Anandrao; Durgawale, Prakash M. (Journal of Neonatal Surgery, 2025)
Background: Aging is a natural and progressive biological process characterized by a decline in physiological and mental capacities, increasing susceptibility to diseases and mortality. The World Health Organization emphasizes the growing proportion of the elderly population worldwide, driven by reduced birth rates and improved healthcare systems. This demographic shift necessitates a better understanding of the elderly's health status and quality of life, particularly across diverse settings. Objectives: The study aimed to: (1) estimate the proportion of the elderly population in urban and rural areas; (2) analyze and compare their morbidity status and its association with socio-demographic variables; (3) evaluate and contrast their quality of life; and (4) recommend strategies for improving elderly health in different environments. Methodology: A community-based cross-sectional study was conducted in the Satara District of Maharashtra, India. Using a multistage sampling technique, 3,300 elderly individuals (aged ≥60 years) from both urban and rural areas were included, targeting a 90% response rate. Data were collected using pre-validated tools after obtaining informed consent. Both descriptive and inferential statistics, including independent t-tests and Mann-Whitney U tests, were applied for analysis. Results: Most participants were aged 60–69 years with no significant age or gender variation between urban and rural areas. Quality of life was significantly better among the rural elderly, especially in mental health and social domains. Gender differences were significant only in the "Senses" domain (p = 0.043). Conclusion: Socioeconomic conditions and family support significantly influence the quality of life among the elderly, with rural populations faring better than urban counterparts.